Akustične lastnosti bukovine po hidrotermični obdelavi - Ervin Žveplan; Aleš Straže (Les, 2017)
We investigated the acoustic properties of beech wood (Fagus sylvatica L.) after hydrothermal treatment. Two beech logs were cut into 10 pairs of radially oriented specimens with the dimensions 500 mm × 160 mm × 12 mm and air dried. Specimens were thermally treated for 1 hour in saturated vapour pressure atmosphere at 135 °C. After the treatment the specimens were conditioned at 20 °C and 50 % RH and their wood density, speed of ultrasound in all directions and colour properties in CIELab colour space were determined. Free flexural vibration tests were used afterwards to determine the acoustic properties of wood. We defined acoustic coefficient (K), damping of sound (tan δ) and relative acoustic conversion efficiency (RACE). The study confirmed a significant decrease of wood density after the hydrothermal processing. The increase in speed of ultrasound in hydrothermally-treated wood caused no change in the modulus of elasticity in all anatomical directions. Mechanical anisotropy of wood decreased slightly after the treatment. The colour measurements of specimens showed a linear correlation between the total colour change and change of wood density and stiffness. The acoustic properties of hydrothermally treated beech wood were partly improved due to the increase in the specific modulus of elasticity and the acoustic coefficient combined with the decrease in vibration damping.